Probabilistic physics of failure approach to reliability : modeling, accelerated testing, prognosis and reliability assessment /: modeling, accelerated testing, prognosis and reliability assessment. (2017) - Modarres, M (Mohammad); Amiri, Mehdi; Jackson, Christopher
No abstract available